Influence of staphylococcal Phage SAvB14 on biofilms, formed by Staphylococcus aureus variant bovis - Y. V. Horiuk; M. D. Kukhtyn; Y. S. Stravskyy; S. I. Klymnyuk; K. M. Vergeles; V. V. Horiuk (Regulatory Mechanisms in Biosystems, 2019)
The use of bacteriophages for the treatment of chronic inflammatory processes has proved to be relevant, especially during isolation of antibiotic-resistant pathogens formed in biofilms. The article presents the results of research on the influence of Phage SAvB14 on young and mature biofilms formed by Staphylococcus aureus variant bovis. In the experiments we used cultures of S. aureus and a specific Phage SAvB14 isolated from the secretion of the mammary gland of cows suffering from chronic mastitis. In the study of the influence of bacteriophage on formed biofilms we determined the optical density of the dye solution that was washed from the biofilm photometrically on a spectrophotometer PE-5400UV (Ecroskhim, Russia) and the number of staphylococcal cells in the biofilm after the action of the bacteriophage on 24-hour and 72-hour biofilms by a ten-fold dilution on beef-extract agar. It was determined that under the influence of the bacteriophage on young 24-hour biofilms of S. aureus var. bovis, the optical density of the dye solution from biofilm increased within 4 hours up to 10% and the number of microbial cells increased by 1.8 times. After 32 hours of bacteriophage action, the optical density of the dye solution decreased on average by 34% compared to the initial density and the number of S. aureus cells in the biofilm decreased by 30 times. This indicates that microbial cells of young biofilms are not subject to complete lysis during the action of even this specific bacteriophage. Degradation of 77.5% of biofilm under the influence of the bacteriophage was observed on mature 72-hour biofilm within 32 hours at 37 °C. At the same time, viable cells of S. aureus were not isolated from the biofilm. This indicates the high lytic activity of the bacteriophage against mature biofilm bacteria and the possibility of its use in chronic staphylococcal infections caused by S. aureus var. bovis. Thus, the obtained data indicate that when mature 72-hour biofilms are exposed to the researched bacteriophage, their degradation is more intense compared with the young 24-hour biofilms, and the amount of destroyed biofilm was on average 2 times higher. This suggests that the use of specific staphylococcal Phage SAvB14 isolated by us for the destruction of biofilm, formed by S. aureus var. bovis, is promising.